Reflexion und Reflexivität im Kontext Grundschule Perspektiven für Forschung, Lehrer:innenbildung und Praxis - Gläser, Eva; Poschmann, Julia; Büker, Petra; Miller, Susanne (Jahrbuch Grundschulforschung, 2022)
With the end of the 19th century, a debate about the normal and the abnormal also emerged within pedagogy, especially by reference to psychiatric and juridical discourses. Supported by new administrative statistics, discourses and dispositives emerged that aimed not least at normalizing social deviance. This volume traces various discourses on the production of the pedagogical (a)normal between 1900 and 1970 and thus provides an important contribution to difference-theoretical analyses from the perspective of the history of education.